Substrate determinants in the C99 juxtamembrane domains differentially affect γ–secretase cleavage specificity and modulator pharmacology. (18th January 2013) - Ousson, Solenne; Saric, Arman; Baguet, Aurelie; Losberger, Christophe; Genoud, Stephane; Vilbois, Francis; Permanne, Bruno; Hussain, Ishrut; Beher, Dirk
Abstract The molecular mechanisms governing γ‐secretase cleavage specificity are not fully understood. Herein, we demonstrate that extending the transmembrane domain of the amyloid precursor protein‐derived C99 substrate in proximity to the cytosolic face strongly influences γ–secretase cleavage specificity. Sequential insertion of leucines or replacement of membrane‐anchoring lysines by leucines elevated the production of Aβ42, whilst lowering production of Aβ40. A single insertion or replacement was sufficient to produce this phenotype, suggesting that the helical length distal to the ε–site is a critical determinant of γ‐secretase cleavage specificity. Replacing the lysine at the luminal membrane border (K28) with glutamic acid (K28E) increased Aβ37 and reduced Aβ42 production. Maintaining a positive charge with an arginine replacement, however, did not alter cleavage specificity. Using two potent and structurally distinct γ–secretase modulators (GSMs), we elucidated the contribution of K28 to the modulatory mechanism. Surprisingly, whilst lowering the potency of the non‐steroidal anti‐inflammatory drug‐type GSM, the K28E mutation converted a heteroaryl‐type GSM to an inverse GSM. This result implies the proximal lysine is critical for the GSM mechanism and pharmacology. This region is likely a major determinant for substrate binding and we speculate that modulation of substrate binding is the fundamental mechanism by which GSMs exert their action.